Factors Affecting the Intercultural Adaptation Process of International Students: A Case Study of Vietnamese Postgraduate Students at a Tertiary Institution in Taiwan - Ngo, Cong Lem (H. : ĐHQGHN, 2019)
The study was conducted to explore challenges Vietnamese postgraduate students were confronted with during their intercultural adaptation process in Taiwan. The participants (N = 28) were administered an open-ended questionnaire, probing into different aspects of their intercultural adjustment, namely academic, psychological and sociocultural issues. Findings indicated regarding academic life, the sojourn students encountered language barriers (both in English and Chinese), new pedagogical approach, examination and publication pressure. Other adjustment problems involved daily communication with the local, unfamiliar diet, homesickness, perceived discrimination, and few activities for international students. Implications for relevant stakeholders were discussed.